'Calling out' corporate redwashing: the extractives industry, corporate social responsibility and sport for development in indigenous communities in Canada. Issue 12 (2nd December 2019) - Millington, Rob; Giles, Audrey R.; Hayhurst, Lyndsay M.C.; van Luijk, Nicolien; McSweeney, Mitchell
Abstract: In this paper, we explore the sponsorship of sport for development (SFD) programs in Indigenous communities in Canada by oil, gas, and mining companies (the 'extractives industry'). While SFD programming has recently proliferated, the majority of these initiatives have been located in 'developing' countries of the global South. It is only more recently that SFD programs have gained traction in Canada, particularly in Indigenous communities. In undertaking an analysis of corporate social responsibility reports, we explore the tensions in having private companies — particularly those with poor environmental and social records — fund SFD programs in Indigenous communities. In the vein of 'green-washing', we argue that extractives companies are funding SFD programs in Indigenous communities as a form of 'redwashing' to portray themselves as good corporate citizens and as members of the communities in which they operate, while obfuscating the harmful impacts of extractive practices and histories of colonialism.